The Main Themes of Ouyang Xiu’s Epigraphy - Степанова, Екатерина (Acta Orientalia Vilnensia, 2003)
The article investigates some “you ji” - “inscriptions of traveller” by Ouyang Xiu (1007-1072), a poet and official of the Northern Sung Dynasty in China (968-1127). The article opens with a brief description of the tradition of inscriptions in China and the peculiarities of inscriptions “you ji”. This genre was widely popular in the 11th century, Confucian officials wrote inscriptions on their way to employment places in provinces. Temples, schools, arbours, towers, parks were decorated with such kind of inscriptions. Usually a famous literary man was invited for writing. In Ouyang Xiu’s heritage there are about thirty inscriptions “you ji”. Translations with comments of some texts are included. The main themes of Ouyang Xiu’s inscriptions deal with relations between person and nature, customs of remote places and provinces, historical persons and the author’s contemporaries.